Periodic moving waves on 2D lattices with nearest-neighbor interactions - Fečkan, M. (Ukrains’kyi Matematychnyi Zhurnal, 2008)
We study the existence of periodic moving waves on two-dimensional periodically forced lattices with linear coupling between nearest particles and with periodic nonlinear substrate potentials. Such discrete systems can model molecules adsorbed on a substrate crystal surface.